1997
DOI: 10.1007/s004330050065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 99mTc-citrate, 67Gacitrate and 99mTc(V) dimercaptosuccinic acid for the scintigraphic visualization of acute appendicitis

Abstract: An experimental study was planned to evaluate 99mTc-citrate, 67Ga-citrate and 99mTc(V) dimercaptosuccinic acid (DMSA) as agents for the visualization of acute appendicitis. Appendiceal ligation was performed through a midline incision in 24 rabbits. Twenty-four hours later the animals were divided into three equal groups. The rabbits were injected through the aurical vein with 1 mCi (37 MBq) 99mTc-citrate in group I, 0.5 mCi (18.5 MBq) 67Ga-citrate in group II and 1 mCi (37 MBq) 99mTc(V) DMSA in group III. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
(20 reference statements)
0
4
0
4
Order By: Relevance
“…Batın tekrar dikilerek kapatılır. On iki saat sonra akut apandisit modeli gelişir (22). Bazı çalışmalarda lümen içine bakteri enjeksiyonu da yapılmıştır.…”
Section: Deneyhayvanlarındaoluşturulanenfeksiyon Modelleriunclassified
See 1 more Smart Citation
“…Batın tekrar dikilerek kapatılır. On iki saat sonra akut apandisit modeli gelişir (22). Bazı çalışmalarda lümen içine bakteri enjeksiyonu da yapılmıştır.…”
Section: Deneyhayvanlarındaoluşturulanenfeksiyon Modelleriunclassified
“…Ga-67 sitrat, demire benzer şekilde sideroforlara da yoğun bağlanma gösterir. Ga-67 sitrat enfekte dokularda mikroorganizmalar tarafından üretilen sideroforlar tarafından tıpkı demirmiş gibi alınır ve hücre içine taşınır (22). Ga-67'nin yüksek gama enerjisi, uzun yarı ömrü, hastalarda yüksek radyasyon maruziyetine sebep olur, enjeksiyondan sonra uzun görüntüleme sürelerine ihtiyaç vardır.…”
Section: Spectgörüntülemeunclassified
“…Yedi çalışma laparoskopik apandektomide güdük kapatma yöntemleriyle (33,107,(298)(299)(300)(301)(302)307) , 2 çalışma apandisit tanısında idrarda 5-hidroksiindol asetik asit (5-HİAA) düzeyinin güvenilirliği ile (139,140) , 2 çalışma apandisitte oksidatif doku hasarı varlığının araştırılmasıyla (285,306) 2 çalışma da apandisit dahil olmak üzere karın içi yangısal değişikliklerin tanısında sintigrafinin yararıyla (282,283) .…”
Section: Genel öZelliklerunclassified
“…Sintigrafi: Şüpheli olgularda gereksiz apandektomi sıklığını azaltmada yararlı olabileceği (104) , diğer yön-temlerle tanı hala şüpheli ise kullanılabileceği (284) öne sürülmüş ve deneysel çalışma ile apandisit olguları için 99mTc sitrat'ın DMSA ve 67Ga sitrattan daha üstün olduğu bildirilmiştir (282,283) .…”
Section: Manyetik Rezonans Görüntüleme (Mr)unclassified
“…Pentavalent DMSA exhibited less plasma protein binding; in mice greater bone and muscle uptake, and lower kidney and liver uptake were observed with respect to trivalent DMSA [177]. The results indicated that 99m Tc-citrate is preferable to the other agents due to higher concentration ratios and absence of radioactivity in the abdominal organs facilitating correct diagnosis [187]. We evaluated it for imaging inflammatory lesions in experimental animals in comparison to 99m Tc(III) DMSA and 99m Tc-HIG [180].…”
Section: Radiolabelled Macromolecules Polyclonal Human Immunoglobulinmentioning
confidence: 99%